A combined thermodynamics and first principles study of the electronic, lattice and magnetic contributions to the magnetocaloric effect in La0.75Ca0.25MnO3 - Korotana, R. K.
Manganites with the formula La1-xCaxMnO3 for 0.2 < x < 0.5 undergo a magnetic field driven transition from a paramagnetic to ferromagnetic state, which is accompanied by changes in the lattice and electronic structure. An isotropic expansion of the La0.75Ca0.25MnO3 cell at the phase transition has been observed experimentally. It is expected that there will be a large entropy change at the transition due to its first order nature. Doped lanthanum manganite (LMO) is therefore of interest as the active component in a magnetocaloric cooling device. However, the maximum obtained value for the entropy change in Ca-doped manganites merely reaches a moderate value in the field of a permanent magnet. The present theoretical work aims to shed light on this discrepancy. A combination of finite temperature statistical mechanics and first principles theory is applied to determine individual contributions to the total entropy change of the system by treating the electronic, lattice and magnetic components independently. Hybrid-exchange density functional (B3LYP) calculations and Monte Carlo simulations are performed for La0.75Ca0.25MnO3. Through the analysis of individual entropy contributions, it is found that the electronic and lattice entropy changes oppose the magnetic entropy change. The results highlighted in the present work demonstrate how the electronic and vibrational entropy contributions can have a deleterious effect on the total entropy change and thus the potential cooling power of doped LMO in a magnetocaloric device.